Desain Mesin Pencacah Sampah Organik Kapasitas 20 Kg dalam Mendukung Produksi Eco-Enzyme dan Kompos - Sundari, Susanti; Yuspradana, Rizky; Irwanto, Sofyan; Pratama, Rio Aditiya (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Research to design an organic waste chopping machine with a capacity of 20 kg, which can be used by small industries and households, aims to facilitate the processing of organic waste with a capacity that is not large to support the activities of processing fruit and vegetable waste into eco-enzyme or compost which is an alternative organic waste processing solutions. During this process, what is done is to cut fruit and vegetable waste into small pieces which will be processed into eco-enzyme using a kitchen knife which is definitely not effective, takes a long time and the results are not uniform. The method used in designing this tool is the French method. This research succeeded in designing an organic waste chopping machine with a capacity of 20 kg, with a motor power of 0.18 kw / 180 watts. The combination of tool capacity and low watt motor makes mobility easier because it is easy to move and saves electricity consumption or costs. This research is a solution for processing organic waste both in households and in communities that are eco-enzyme and compost activists with real implementation in supporting more effective and efficient handling of organic waste.